Crystal structure of the channel-forming polypeptide antiamoebin in a membrane-mimetic environment - Karle, Isabella L. (The National Academy of Sciences, 1998)
Crystals of an ion-channel-forming peptaibol peptide in a partial membrane environment have been obtained by cocrystallizing antiamoebin with n-octanol. The antiamoebin molecule has a bent helical conformation very similar to that established for Leu-zervamicin, despite a significantly different sequence for residues 1–8. The bent helices assemble to form a polar channel in the shape of an hour glass that is quite comparable to that of Leu-zervamicin. The molecules of cocrystallized octanol are found in two different areas with respect to the assembly of peptide molecules. One octanol molecule mimics a membrane segment along the hydrophobic exterior of the channel assembly. The other octanol molecules fill the channel in such a way that their OH termini satisfy the C=O moieties directed into the interior of the channel. Structure parameters for C(82)H(27)N(17)O(20)⋅3C(8)H(18)O are space group P2(1)2(1)2(1), a = 9.143(2) Å, b = 28.590(8) Å, c = 44.289(8) Å, Z = 4, agreement factor R(1) = 11.95% for 4,113 observed reflections [>4σ(F)], resolution ∼1.0 Å.